BIODIESEL PRODUCTION FROM PALM OIL MILL EFFLUENT BY USING THERMOMYCES LANUGINOSUS LIPASE AS A CATALYST - Rachmadona, Nova (KINETIKA, 2017)
Biodiesel production via enzymatic transesterification using Palm Oil Mill Effluent (POME) as the raw material and Thermomyces lanuginosus lipase (TLL) as the catalyst is proposed in this study. POME is one of the waste water discharged from the sterilization process, crude oil clarification process and cracked mixture separation process of palm oil in mills. POME contains a high amount of organic matter, oil and grease, total solids and suspended solids. POME could be an alternative raw material for producing biodiesel because of its high oil and fat content that could be converted into biodiesel. High Free Fatty Acid (FFA) makes the conversion seems impossible because if using chemical transesterification, it will form saponification. Enzymatic transesterification is the solution for this problem. In this study, the conditions for biodiesel production included lipase content of 0.3%, a methanol/oil molar ratio of 6:1, a water content of 4.7%, a stirring speed of 500 rpm, a reaction temperature of 30 Â°C and a reaction time of 24 hour. The biodiesel yield was achieved at 81.87%%.